PERCAMPURAN BUDAYA JAWA DAN CINA: Harmoni dan Toleransi Beragama Masyarakat Lasem - Atabik, Ahmad (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
This article explores the fact of harmony and religious tolerance values of the culture assimilation of Tionghoa ethnic dan local people in Lasem. Tionghoa ethnic have lived in Lasem since XI Century. Their existence bear new culture and plurarity for Lasem people that leads to a religiocity and social harmony within the people. The harmonius relation is proven when their both fight against Dutch Collonials in Lasem. The harmonious and tolerance of Lasem moslems can be seen in the interaction of the local people and the newcomer (Tionghoa ethnic), whether they are muslim or not